The politics of vacancy: Housing struggles and collective action in rural Greece – the case of HARTA (Radical Housing Journal)
This article traces the political and activist journey of HARTA, a collective born in the small municipality of Naousa, Greece, amid a crisis of housing precarity, migrant displacement, and rural decline. Against a backdrop of manufactured scarcity, abandoned properties, and exclusionary politics of inertia, HARTA mobilized local knowledge, fieldwork, and solidarity to expose the political choices behind housing deprivation. Through mapping, occupation, and the exercise of social power, they confronted both visible and invisible forms of homelessness and challenged the ideological foundations of familistic property and belonging. By narrating their struggle, HARTA asks a broader question: How can land and residential vacancies be reclaimed as terrains of social justice and collective agency in rural Greece?